STUDENTS’ LIVED EXPERIENCE OF LEARNING ENGLISH THROUGHT TEAM GAMES TOURNAMENT AT THE TENTS GRADE OF SMK NEGERI 1 SIANTAR - Thesa Laora Miranda Siahaan; Deswita Fitriani Samosir; Heltri Fildayanti Samongilailai; Dumaris Silalahi (JR-ELT (Journal of Research in English Language Teaching), 2025)
Previous research on Teams Games Tournament (TGT) has been dominated by a quantitative focus on learning outcomes, creating a gap in understanding the affective and psychosocial aspects of learning. This qualitative phenomenological study aims to describe the lived experiences of tenth-grade students at SMK Negeri 1 Siantar in learning English through the TGT model. Through phenomenological interviews with 35 students, this study identified five essential themes: (1) Motivation and Learning Enjoyment, (2) Teamwork and Sense of Connectedness, (3) Competition and Emotional Pressure, (4) Independence and Self-Reflection, and (5) Meaningful Learning. The findings reveal that the dynamics of TGT effectively fulfill the Three Basic Psychological Needs in Self-Determination Theory (SDT): Relatedness, Competence, and Autonomy. Overall, students perceive TGT as a “living” and meaningful learning experience, as it integrates academic aspects with the development of soft skills such as collaboration and confidence.